Leveraging Digital Resources: A Resource-Based View Perspective - Willie, Michael (Manunggal Halim Jaya, 2025)
In today's rapidly evolving digital landscape, organisations are challenged to strategically deploy digital resources to secure competitive advantage. Drawing upon the Resource-Based View (RBV) theory, this paper explores the intricate interplay between digital resources and organisational success. Through thematic analysis of empirical literature, the study delves into key facets such as data utilisation, digital platforms, technological capabilities, talent management, agility, and strategic partnerships. Methodologically, qualitative research techniques, notably thematic analysis, are employed to synthesise existing research findings. The study uncovered that human capital is pivotal in propelling digital transformation and fostering innovation. Organisational success in the digital era relies on implementing effective methods for managing digital talent, including recruiting, training, and keeping workers with digital competence. The study also highlights the strategic significance of digital resource utilisation within the RBV framework. Finally, the paper presents practical implications for organisational leaders seeking to harness digital resources effectively to achieve sustainable competitive advantage in the digital era. Findings underscore the strategic importance of digital resource utilisation in enhancing organisational competitiveness and driving long-term growth. The study contributes to understanding how organisations can optimally leverage digital resources within the RBV framework.